(untitled) (Swiss Medical Weekly, 2017)
Understanding how best to manage the complex healthcare needs of hospitalised, mostly multimorbid medical patients is an international priority. Healthcare should be effective, safe and provide high quality at a reasonable cost. However, basic logistic and organisational issues of medical ward-based care have received less attention than the medical treatment of specific pathologies. Consequently, we still use old-fashioned care and transition procedures for medical inpatients. This contrasts with dynamic developments in other, non-healthcare industries, where process optimisation is a major part of innovation. Promising new approaches to better align healthcare needs of hospitalised medical patients from clinical trials will help to advance the field significantly. Healthcare costs attributable to the aging, multimorbid population are rising worldwide. One cost driver is the high resource use of in-hospital treatment. In view of the expected demographic evolution of an aging population, better resource allocation is important. As in other countries, the Swiss healthcare system is in the midst of transformation aiming to improve health outcomes of patients at an affordable cost. One important area of redesign is identifying the best setting for diagnosis, treatment and management of acute medical conditions with a shift of in-hospital to outpatient care. Also, safely reducing in-hospital length of stay of inpatient treatment is important, because inpatient care accounts for the largest share of total Swiss healthcare costs. Integration of new technology into these processes holds promises for optimisation. Use of electronic health record-based tools has resulted in improved patient care and patient transitions. But evidence from clinical studies regarding the effect of inter-professional team care interventions on patient relevant outcomes, including activity of daily living, mortality and length of hospital stay, are inconsistent. Thus, there is room for improvement and a need for high quality trials providing evidence on how best to combine technology with innovative transition models for an ameliorated care of medical inpatients. We review in narrative form different transition interventions that have been evaluated for improved medical inpatient care and highlight important patient-centred outcome measures that were investigated. Further, we discuss a novel patient-management tool (In-HospiTOOL), which is currently being evaluated in an ongoing large Swiss multicentre study.